2018
DOI: 10.4236/health.2018.101006
|View full text |Cite
|
Sign up to set email alerts
|

Family Environment Factors to Impact on the Effect of the Smoking Prevention Educational Program for Elementary and Junior High School Students

Abstract: Smoking is a major health problem in many countries. It has been reported on the effects of education on youth with a reduced smoking rate and developed awareness of avoiding smoking verified as a result of educational intervention. The aim of this study was to verify the relationship between sex, school age, and family smoking and the effectiveness of smoking prevention education program (SPEP) as factors that impact the effectiveness of SPEP in elementary school and junior high school students. The participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As reported in previous studies, parental attitudes and educational policies toward smoking have a marked impact on adolescent smoking, indicating that parental smoking serves as a role model for adolescent smoking [3,13,14]. Okuda et al showed that adolescents whose both parents smoke show a stronger tendency to smoke and a greater difficulty to quit than those whose only one or no parent smokes [15]. Therefore, parental smoking is more dangerous than maternal/paternal smoking because it increases second-hand exposure to smoking at home, thus allowing children to develop a positive attitude toward smoking.…”
Section: Discussionmentioning
confidence: 79%
“…As reported in previous studies, parental attitudes and educational policies toward smoking have a marked impact on adolescent smoking, indicating that parental smoking serves as a role model for adolescent smoking [3,13,14]. Okuda et al showed that adolescents whose both parents smoke show a stronger tendency to smoke and a greater difficulty to quit than those whose only one or no parent smokes [15]. Therefore, parental smoking is more dangerous than maternal/paternal smoking because it increases second-hand exposure to smoking at home, thus allowing children to develop a positive attitude toward smoking.…”
Section: Discussionmentioning
confidence: 79%
“…As reported in previous studies, parental attitudes and educational policies toward smoking have a marked impact on adolescent smoking, indicating that parental smoking serves as a role model for adolescent smoking [3,14]. Okuda et al showed that adolescents whose both parents smoke show a stronger tendency to smoke and a greater di culty to quit than those whose only one or no parent smokes [15]. Therefore, parental smoking is more dangerous than maternal/paternal smoking because it increases second-hand exposure to smoking at home, thus allowing children to develop a positive attitude toward smoking.…”
Section: Discussionmentioning
confidence: 80%